Temples in Syria in Classical Ages (Greek-Roman) between inherited and Foreign A Case Study of The Temples of Palmyra and The Southern Region (Damascus University Journal for engineering sciences, 2023)
The temple is the cultural center of each nation, in which reflects its beliefs and The temple in Syria has always had a distinguished culmination.In the old ages(the bronze and iron eras), the ancient Syrian civilization crystallized a system of its own temples which had an important architectural characteristics, these characteristics the research called them inherited architectural characteristics and worked on classifying them.Then another civilizations entered Syria, such as the Greek and Roman civilizations, which are called classical civilizations, and they brought with them the architectural characteristics of their temples, and the research also worked on classifying them.After defining the architectural characteristics of the local Syrian temple and the classical ones which came from the West, and in order to find out whether these incoming characteristics have dominated the Syrian temple or subjugated it in turn, the research will move to studies the Syrian temple in the classical period (Greek and Roman) and refutes its architectural characteristics through two case studies of the Palmyra temples and the southern region, to be able to determine what is local, and what is classical in the architecture of the Syrian temples in classical period.Finally, the research makes a study comparison between the classical Greek and Roman temple, and the Syrian temple in that period, so that the research can reach general results related to the comparative study, The research ends with recommendations
Keywords: The Temple; Syria; Classical Periods; Greece; Romans; Local; Inherited; Foreign; Palmyra; Southern Region